The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0234271
|View full text |Cite
|
Sign up to set email alerts
|

Single versus dual antiplatelet therapy following peripheral arterial endovascular intervention for chronic limb threatening ischaemia: Retrospective cohort study

Abstract: Objectives Antiplatelet therapy following peripheral arterial endovascular intervention lacks high quality evidence to guide practice. The aim of this study was to assess the effect of three months of dual antiplatelet therapy on amputation-free survival following peripheral arterial endovascular intervention in patients with chronic limb threatening ischemia. Methods A retrospective review of symptomatic patients undergoing primary peripheral arterial endovascular intervention over a seven-year period was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
2
1
1
Order By: Relevance
“…One study showed lower 5-year MALE and MACE rates when DAPT was prescribed for >6 months compared with <6 months or SAPT [23]. A recently published study, similar to ours, compared 3-month DAPT with SAPT and showed no significant difference in amputation-free survival [24]. Different from our study, it included a high proportion of patients treated for aorta-iliac lesions and only a few patients with stents.…”
Section: Discussioncontrasting
confidence: 44%
“…One study showed lower 5-year MALE and MACE rates when DAPT was prescribed for >6 months compared with <6 months or SAPT [23]. A recently published study, similar to ours, compared 3-month DAPT with SAPT and showed no significant difference in amputation-free survival [24]. Different from our study, it included a high proportion of patients treated for aorta-iliac lesions and only a few patients with stents.…”
Section: Discussioncontrasting
confidence: 44%
“…After careful analysis of these articles, one study without any long-term outcomes, two studies where control groups were absent, and one study designed to compare unrelated drugs, were excluded at the final stage. Finally, ten full-text articles, including three RCTs [ 23 , 24 , 25 ], three NRCTs with propensity-score-weighted matching (PSM) [ 26 , 27 , 28 ], and four NRCTs [ 29 , 30 , 31 , 32 ], were retrieved for quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In the four NRCTs, the use of an allocation method other than randomization means that these groups were unlikely to be comparable, which resulted in increased selection bias; three of the articles performed PSM to reduce treatment selection bias and adjust for confounding variables related to NRCTs [ 33 ]. The overall risk of bias was low in one NRCT [ 26 ], moderate in five NRCTs [ 27 , 28 , 29 , 30 , 31 ], and serious in one NRCT [ 32 ]. Publication bias was analyzed using funnel plots, and this revealed no obvious asymmetry regarding each investigated outcome ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A retrospektív vizsgálatok eredményei azonban nem egységesek. Egy további vizsgálatban az endovascularis beavatkozást követő három hónapos kettős gátlás nem bizonyult hatásosabbnak az amputációmentes túlélés vonatkozásában [50]. Mindazonáltal a perifériás intervenciókat követő időszakban kimutatták azt is, hogy ez a stratégia valamelyest jótékonyabb volt a túlélés vonatkozásában [51].…”
Section: A Kettős Thrombocytaaggregáció-gátlás Lehetőségeunclassified